Age differences in fatigue, decrements in energy, and sleep disturbance in oncology patients receiving chemotherapy. (August 2016) - Bischel, Lindsey E.; Ritchie, Christine; Kober, Kord M.; Paul, Steven M.; Cooper, Bruce A.; Chen, Lee-May; Levine, Jon D.; Hammer, Marilyn; Wright, Fay; Miaskowski, Christine
Abstract: Objective: The number of older adults with cancer is increasing. Given the limited amount of research and the inconsistent findings regarding age differences in common physical symptoms associated with cancer and its treatments, the purposes of this study, in a sample of oncology outpatients receiving chemotherapy (CTX), were to evaluate for age differences in demographic and clinical characteristics, as well as in occurrence rates of and severity ratings for fatigue, decrements in energy, and sleep disturbance. In addition, using regression analysis techniques, within and across age groups, demographic and clinical characteristics associated with the severity of each symptom were evaluated. Methods: Patients (n = 1343) were dichotomized into younger (<65 years) and older (≥65 years) age groups. Patients completed self-report questionnaires prior to their next dose of CTX. Results: Overall, our findings suggest that compared to younger patients, older adults experience a lower or similar level of fatigue, decrements in energy, and sleep disturbance. However, it should be noted that both age groups experienced high occurrence rates and moderate to severe levels of all three symptoms. Conclusions: Clinicians need to assess all oncology patients receiving CTX for these three symptoms. Future research needs to determine the biopsychosocial reasons that underlie these age-related differences in fatigue, decrements in energy, and sleep disturbance. Highlights: Both younger and older oncology patients report high levels of all three symptoms. Regardless of age, poorer functional status was associated with more severe symptoms. Clinicians need to assess for fatigue, decrements in energy, and sleep disturbance.